Sprawa rozmieszczenia wojsk ONZ na terenie Konga (15 lipca – 12 sierpnia 1960) - Sołtysiak, Jakub (Acta Universitatis Lodziensis. Folia Historica, 2007)
On 19 June 1960 the UN Security Council passed the resolution no 143 (1960), which enabled the start of the UN Operation in Congo - Operation des Nations Unies Au Congo (ONUC). The operation was to consist of two parts: civilian and military, foreseeing sending UN Armed Forces to Congo. The deployment of UN soldiers in Congo was subject of much controversy at the UN forum. The first month of UN soldiers involvement in Congo’s crisis was of crucial importance for defining the character of the military operation. Controversies arose about the powers of UN soldiers, and the way of placement of Peace Forces in Katanga. The group of countries put pressure to settle the conflict by force. The additional problem was the desire of world powers, competing for influence in Africa, to use the whole conflict to achieve vested interests. There was no agreement as to the way the UN soldiers and their powers were to be used in the face of key Congo’s problems. In that case the character of UN Operation in Congo was brought up for an international discussion. As a result of this discussion, and due to determination of UN Secretary – General Dag Hammarksjold, supported by American diplomacy, the international character of UN military operation was kept. Not using UN Forces to immediate political goals was another success. Despite different pressures, Hammarksjold managed to deploy UN Military Forces to Katanga by means of diplomatic and peaceful methods, exclusively.